Politics and power in early medieval Europe : Alsace and the Frankish Realm, 600-1000 - Hummer, Hans J. (Cambridge, UK ; New York : Cambridge University Press, 2005)
Taking Alsace as its focus, this innovative study offers a unique snapshot of localised and centralised political structures in early medieval Europe. Providing a comprehensive exploration of the regional sources, it tracks the development and eventual demise of a distinctive political culture derived from networks of monasteries and kin-groups.
1. The late Merovingian order -- 2. Conquest and continuity -- 3. The Carolingians and ecclesiastical property -- 4. Reaction and resistance -- 5. The politics of Old German -- 6. Imperial unity and regional power -- 7. The late Carolingian order -- 8. The tenth-century transformation -- 9. Conclusions -- App. Records of the dispute between Rodoin and Gebahart and the monastery of Weissenburg.
Includes bibliographical references (pages 262-286) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Alsace (France) -- History; Alsace (France) -- Politics and government; Europe -- Politics and government -- 476-1492.; Alsace (France) -- Histoire; Alsace (France) -- Politique et gouvernement; Europe -- Politique et gouvernement -- 476-1492.; HISTORY; Politics and government; Europe; France -- Alsace; Macht; Zentralgewalt; Mittelalter; Elsass; Fränkisches Reich; Frankische rijk; Politieke macht; 476-1492; History